Employing Copper-Based Nanomaterials to Combat Multi-Drug-Resistant Bacteria - Yujie Zhai; Zhuxiao Liang; Xijun Liu; Weiqing Zhang (Microorganisms)
The rise of multi-drug-resistant (MDR) bacteria poses a severe global threat to public health, necessitating the development of innovative therapeutic strategies to overcome these challenges. Copper-based nanomaterials have emerged as promising agents due to their intrinsic antibacterial properties, cost-effectiveness, and adaptability for multifunctional therapeutic approaches. These materials exhibit exceptional potential in advanced antibacterial therapies, including chemodynamic therapy (CDT), photothermal therapy (PTT), and photodynamic therapy (PDT). Their unique physicochemical properties, such as controlled ion release, reactive oxygen species (ROS) generation, and tunable catalytic activity, enable them to target MDR bacteria effectively while minimizing off-target effects. This paper systematically reviews the mechanisms through which Cu-based nanomaterials enhance antibacterial efficiency and emphasizes their specific performance in the antibacterial field. Key factors influencing their antibacterial properties—such as electronic interactions, photothermal characteristics, size effects, ligand effects, single-atom doping, and geometric configurations—are analyzed in depth. By uncovering the potential of copper-based nanomaterials, this work aims to inspire innovative approaches that improve patient outcomes, reduce the burden of bacterial infections, and enhance global public health initiatives.